Rhetoric and sociolinguistics in times of global crisis - Hanci-Azizoglu, Eda, 1978-; Alawdat, Maha, 1971- (Advances in linguistics and communication studies (ALCS) book series., 2021)
"The purpose of this book is also to bridge the gap to initiate a discussion on understanding how rhetoric and sociolinguistics could create critical awareness for individuals, societies and learning environments during crisis times"--